Influence of optical band gap and particle size on the catalytic properties of Sm/SnO2–TiO2 nanoparticles. (June 2015) - Javaid, Shaghraf; Farrukh, Muhammad Akhyar; Muneer, Iqra; Shahid, Maryam; Khaleeq-ur-Rahman, Muhammad; Umar, Akrajas Ali
Highlights: Sm/SnO2 –TiO2 nanoparticles were prepared by using sol–gel, ultrasonic and hydrothermal method. Band gap was calculated by using data from solid phase spectroscopy to study optical properties. Enhanced red shift in the optical band gap (shifting of wavelength to visible region) was observed. A direct relationship between particle size and optical band gap was investigated. It was observed that Sm reduced the optical band gap and increased catalytic efficiency when supported on SnO2 /TiO2 . Abstract: In this work, samarium (Sm) supported on tin oxide–titanium oxide (SnO2 /TiO2 ) nanoparticles (Sm/SnO2 –TiO2 ) were synthesized by sol–gel, ultrasonic and hydrothermal methods; and the optical and catalytic properties of Sm/SnO2 –TiO2 nanoparticles was observed. Effect of synthetic methods on nanoparticles size and percentage composition of anatase and rutile phase in TiO2 was evaluated. The Sm/SnO2 –TiO2 nanoparticles were characterized by Transmission Electron Microscopy, Scanning Electron Microscopy, Energy Dispersive X-ray spectroscopy, Powder X-ray Diffraction, Thermogravimetric Analysis and Fourier Transmission Infrared Spectroscopy. However, UV–Vis and solid phase spectroscopy were used to determine the catalytic efficiency and optical band gap, respectively. It was found out that nanoparticles synthesized by sol–gel and hydrothermal method have small optical band gap as compare to nanoparticles synthesized by ultrasonic method and ultimately showed more catalytic activity toward degradation of dye due to red shift in the optical band gap (shifting of wavelength to visible region). A direct relationship between particle size and optical band gap was investigated. It was observed that Sm reduced the optical band gap and increased catalytic efficiency when supported on SnO2 /TiO2 .